Correlation between abnormal GSK3β, β Amyloid, total Tau, p-Tau 181 levels and neuropsychological assessment total scores in CKD patients with cognitive dysfunction: Impact of rHuEPO therapy. (November 2019) - Vinothkumar, G.; Krishnakumar, S.; Riya,; Venkataraman, P.
Highlights: Cognitive dysfunction has been increasingly recognized in CKD patients. Platelet GSK3β has been a focus of the growing literature on blood based biomarkers for cognitive dysfunction. Increased platelet GSK3β leads to cause Aβ production and hyper phosphorylation of Tau. Platelet GSK3β and its connecting with plasma Aβ and pTau levels in CKD patients with cognitive dysfunction. Abstract: Background: Cognitive dysfunction potentially affecting up to 60% of CKD patients. GSK-3β plays a key role in the pathogenesis of AD and Cognitive dysfunction, contributing to Aβ production and Aβ-mediated neuronal death by phosphorylating tau inducing hyperphosphorylation in paired helical filaments. However, studies have shown that plasma p-Tau181 is more specific for AD and cognitive dysfunction. Anemia is a vital risk factor for cognitive dysfunction in CKD patients. EPO is usually to treat anemia in CKD and also improved in cognitive function. The aim of the study is to correlate between the impacts of rHuEPO therapy on platelet GSK3β expression, plasma Aβ, total Tau, p-Tau 181 levels and neuropsychological assessments total scores in CKD patients with Cognitive dysfunction. Methods: The subjects, 30 CKD without cognitive dysfunction and 30 CKD with cognitive dysfunction patients. To correlate abnormal proteins with neuropsychological tests scoring in CKD with cognitive dysfunction subjects after the six months rHuEPO therapy. Results: The p < 0.05 is considered as statistically significant. Pearson and Spearman correlation coefficient was used to determine the potential relationship between abnormal proteins with neuropsychological tests scoring in respective experimental groups. Conclusions: The use of abnormal protein levels, preferably in association with neuropsychological assessment total scores, appears to be a potential tool that can improve the CKD with cognitive dysfunction diagnosis. In post rHuEPO treatment, the altered protein abnormalities and neuropsychological assessment scores were retrieved significantly compared to pre treatment determined the clinical usefulness of rHuEpo as supplemental therapeutic agent in cognitive dysfunction in CKD.